Information Security and Organizational Performance: Empirical Study of Korean Securities Industry. Issue 2 (1st April 2015) - Kong, Heekyung; Jung, Suhyun; Lee, Insung; Yeon, Seung‐Jun
Abstract : This study was conducted to analyze the effect of information security activities on organizational performance. With this in mind and with the aim of resolving transaction stability in the securities industry, using an organization's security activities as a tool for carrying out information security activities, the effect of security activities on organizational performance was analyzed. Under the assumption that the effectiveness of information security activities can be bolstered to enhance organizational performance, such effects were analyzed based on Herzberg's motivation theory, which is one of the motivation theories that may influence information protection activities. To measure the actual attributes of the theoretical model, an empirical survey of the securities industry was conducted. In this explorative study, the proposed model was verified using partial least squares as a structural equation model consisting of IT service, information security, information sharing, transaction stability, and organizational performance.